A Community Choir Intervention to Promote Well-Being Among Diverse Older Adults: Results From the Community of Voices Trial. (9th November 2018) - Johnson, Julene K; Stewart, Anita L; Acree, Michael; Nápoles, Anna M; Flatt, Jason D; Max, Wendy B; Gregorich, Steven E
Abstract: Objectives: To test effects of the Community of Voices choir intervention on the health, well-being, and health care costs of racial/ethnically diverse older adults. Method: Twelve Administration-on-Aging-supported senior centers were cluster randomized into two groups: the intervention group started the choir immediately and a wait-list control group began the choir 6 months later. The choir program was designed for community-dwelling adults aged 60 years and older. The multimodal intervention comprises activities that engage participants cognitively, physically, and socially. Outcome measures assessed these three domains as well as health care utilization and costs. The intention-to-treat comparison was at 6 months. Results: The sample ( N = 390) had a mean age of 71.3 years ( SD = 7.2); 65% were nonwhite. Six-month retention was 92%. Compared to controls, intervention group members experienced significantly greater improvements in loneliness ( p = .02; standardized effect size [ES = 0.34] and interest in life ( p = .008, ES = 0.39). No significant group differences were observed for cognitive or physical outcomes or for health care costs. Discussion: Findings support adoption of community choirs for reducing loneliness and increasing interest in life among diverse older adults. Further efforts need to examine the mechanisms by which engagement in choirs improves aspects of well-being and reduces health disparities among older adults, including potential longer-term effects. ClinicalTrials.gov Registration: NCT01869179 registered January 9, 2013.